Public reporting of hospital quality data: What do referring physicians want to know?. Issue 11 (November 2018) - Geraedts, Max; Hermeling, Peter; Ortwein, Annette; de Cruppé, Werner
Highlights: Physicians prefer their own and their patients' experiences for hospital referrals. Hospitals' expertise and results of treatment are important as well. Hospitals' structural characteristics and compliance with external requirements play a minor role. Hospital report cards should comprise physicians' and their patients' experiences with hospitals. Abstract: Objective: To identify ambulatory care physicians' priorities for hospital quality criteria to support them in counselling patients what hospital to choose. Methods: Three hundred non-hospital-based stratified randomly sampled physicians, representing the five main referring specialties in Germany participated in a cross-sectional survey. Physicians rated the importance of 80 hospital quality criteria to be used in their counselling of patients in need of hospital care. Criteria selection was based on a literature analysis and the content of Germany's mandatory hospital quality reports. We calculated the most important criteria and performed an ordinal regression analysis to examine whether the physicians' characteristics 'age', 'sex', 'specialty', 'practice type' and 'region' affected physicians' importance ratings. Results: To counsel patients in need of a hospital referral, physicians preferred hospital quality criteria that reflect their own and their patients' experiences with a hospital. Additionally, hospitals' expertise and results of treatment were rated highly important. In contrast, hospitals' structural characteristics and compliance with external requirements were rated less important. Physicians' characteristics affected importance ratings only negligibly. Conclusions: To support referring physicians' counselling of patients regarding what hospital to choose in order to achieve optimal patient outcomes eventually, hospital report cards must be enriched by information on physicians' and their patients' experiences with hospitals. Hospitals' structural characteristics play a minor role in counselling of patients needing hospital care.